Using Rhetorical Flexibility to Bridge Advanced Reading/Writing/Grammar with English 101 - Selvidge, Jenny (Issues in Language Instruction, 2018)
By successfully completing Level 5 of the five-level intensive English program at the Applied English Center (AEC), students can fulfill the university’s ESL requirement and exit the IEP. As a new coordinator to AECR 151, Level 5 Reading/Writing/Grammar, I felt unsure of where students were going after they left the IEP. I knew very little about the English Department and even less about English 101. What were students being asked to do? Were they struggling? Were they thriving? Did we prepare them well? To get a better sense of this, I met with Sonya Lancaster, Associate Director of Freshmen-Sophomore English. Through our discussion, I quickly realized that our students were only being equipped with a specific range of English skills: skills that prepared them to write structurally and grammatically sound essays based on prompts that were given to them. What English 101 requires students to do is to use language to think outside of the box and to use rhetorical flexibility. I was new to this term, but I have now embraced this as one of the central pieces of our L5 writing curriculum.